Glycemic Control and Radiographic Manifestations of Tuberculosis in Diabetic Patients - Chiang, Chen-Yuan; Lee, Jen-Jyh; Chien, Shun-Tien; Enarson, Donald A.; Chang, You-Cheng; Chen, Yi-Ting; Hu, Ting-Yu; Lin, Chih-Bin; Suk, Chi-Won; Tao, Jui-Ming; Bai, Kuan-Jen (PloS one, 2014)
Radiographic manifestations of pulmonary tuberculosis (TB) in patients with diabetes mellitus (DM) have previously been reported, with inconsistent results. We conducted a study to investigate whether glycemic control has an impact on radiographic manifestations of pulmonary TB. Consecutive patients with culture-positive pulmonary TB who had DM in three tertiary care hospitals from 2005-2010 were selected for review and compared with a similar number without DM. Glycemic control was assessed by glycated haemoglobin A1C (HbA1C). A pre-treatment chest radiograph was read independently by two qualified pulmonologists blinded to patients' diabetic status. Films with any discordant reading were read by a third reader. 1209 culture positive pulmonary TB patients (581 with DM and 628 without DM) were enrolled. Compared with those without DM, TB patients with DM were significantly more likely to have opacity over lower lung fields, extensive parenchymal lesions, any cavity, multiple cavities and large cavities (>3 cm). The relative risk of lower lung field opacities was 0.80 (95% CI 0.46-1.42) for those with DM with A1C<7%, 2.32 (95% CI 1.36 - 3.98) for A1C 7%-9%, and 1.62 (95% CI 1.12-2.36) for A1C>9%; and that of any cavity over no cavity was 0.87 (95% CI 0.46-1.62) for patients with DM with A1C<7%, 1.84 (95% CI 1.20-2.84) for A1C 7%-9%, and 3.71 (95% CI 2.64-5.22) for A1C>9%, relative to patients without DM. Glycemic control significantly influenced radiographic manifestations of pulmonary TB in patients with DM.